Spatial Typology of the Greek Territory Based on Transport Accessibility Indicators:A Cartographical Approach Using G. I. S. - Ioannis Katsios; Andreas Tsatsaris; Athina Sakellariou (European Regional Science Association (ERSA), 2006)
Accessing the infrastructure networks, the urban concentrations, the commercial and other activities or key locations, is considered by the spatial planners as a significant and sensitive variable for the territorial analysis. The spatial policies are determined today by the principals of equal and balanced distribution of human resources and activities, as well as by the systematic study of territorial disparities in the deepest territorial analysis detail level possible. The traditional calculative methods of accessibility indicators, does not take into account the entire space of the study area. In the contrary, it's mainly based on calculating the travel cost on linear networks using the "arc-node" topologies. According to these methodologies, the variables (time, distance, or other types of cost) are calculated only for the network elements (nodes, lines). During the recent years, some published studies have appointed the above issue. Accessibility is faced as continuous data thus it is valued and attributed in the entire area of study and not just on the network body. This study's main objective is to generate an accumulative travel cost indicator for the Greek territory, using all major transportation means. In addition the respective spatial typology will be created. The indicator is produced using three distinctive spatial levels representing the three transportation means (land, sea and air transportation). The study's methodology is based on the formation of continuous cost surface model, in raster format, using all the aforementioned transportation nodes. The travel cost value that each cell on the surface will be assigned to, is the absolute time of traveling towards the transportation nodes or towards specific linear network elements. An emphasis is given to the study's cartographic component as well as to the comprehensive use of spatial analysis techniques which are available on GIS software.
Keywords: 330